PENINGKATAN KETRAMPILAN MELALUI PELATIHAN DALAM RANGKA PEMBERDAYAAN SANTRIWATI DI KABUPATEN BANGKALAN - S. Anugrahini Irawati; Bambang Sudarsono (Kompetensi (Competence : Journal of Management Studies), 2014)
This study identifies female students issues after leaving boarding school to the community. research problem is formulated as follows: 1). How Bangkalan interest of female students in the effort to improve quality through empowerment of women. 2) What job or position of interest to students of Bangkalan after leaving boarding school  3) How female students' views toward women's empowerment efforts in Bangkalan. 4). Are the expectations of the female students in order to improve its quality. 5). Any constraints that will be faced by female students in carrying out their duties soon after coming out of boarding school. The results also showed that as many as 470 people became interested in entrepreneurship. Thus, the solution is to provide such training, cooking (culinary), sewing, makeup and handycrafts